KEANEKARAGAMAN JENIS POHON LOKAL DI KAWASAN HUTAN LINDUNG REGISTER 31, KESATUAN PENGELOLAAN HUTAN LINDUNG KOTA AGUNG UTARA, PROVINSI LAMPUNG - Anwar, Saipul; Indriyanto; Asmarahman, Ceng (Jurusan Kehutanan, 2021)
Diversity of local tree species is important in the selection of tree species for reforestation of forest areas. The objectives of this study are to determine the diversity of local tree species, to determine the dominant local tree species and suitable for reforestation in the Register 31 protection forest area, Lampung Province. Data were collected using observational methods and analyzed by descriptive analysis. Furthermore, vegetation analysis is carried out to determine the index of importance value which can then determine the dominance of each local tree population and the diversity of local tree species themselves. The results showed that the most dominant local tree population was durian (Durio zibethinus) with an important value index of 46.5875. The existence of durian trees for all growth phases, including seedlings, poles, saplings, and mature trees, is the most dominant. The local tree species diversity index (H’) was 1.0926. This indicates that the diversity of local tree species in the Register 31 protection forest area is in medium category. Therefore, efforts to enrich local tree species need to be done to maintain the preservation of local tree species in the Register 31 protection forest area, Lampung Province.